2020
DOI: 10.22271/phyto.2020.v9.i1af.10749
|View full text |Cite
|
Sign up to set email alerts
|

Production, processing and marketing related problems faced by orange growers in Chhindwara district of Madhya Pradesh

Abstract: The study was conducted with the objectives to problems faced by Orange Growers in Central India District. The study was purposively conducted in Chhindwara district of Madhya Pradesh where Nagpur mandarin orange is the pride fruit of the region. In all, 200 growers were considered for the study. In production aspect Study revealed that Shortage of irrigation water during summer was top most problem faced by the orange growers, Lack of capital rank second followed by High cost of labour third major problem. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This finding implies that friends and relatives are the major sources of market information for smallholder orange farmers. The finding corresponds with a study by Saryam (2020), who noted that family members, friends, relatives, and progressive farmers were regularly contacted as sources of information. Similarly, Adio et al ( 2016) found that neighbors, friends, family, and village meetings were among the major information sources for farmers.…”
Section: Characteristics Of Respondentssupporting
confidence: 89%
“…This finding implies that friends and relatives are the major sources of market information for smallholder orange farmers. The finding corresponds with a study by Saryam (2020), who noted that family members, friends, relatives, and progressive farmers were regularly contacted as sources of information. Similarly, Adio et al ( 2016) found that neighbors, friends, family, and village meetings were among the major information sources for farmers.…”
Section: Characteristics Of Respondentssupporting
confidence: 89%
“…Horticulture production in India has risen dramatically in recent years. In the past ten years, annual production grew by 4.8%, and the area under horticulture increased by 2.6% [9][10][11]. Apart from ensuring the nation's nutritional security, it also creates new jobs, diversification of farm activities, provides raw materials to various food processing industries and increases farm profitability through increased productivity and foreign exchange earnings.…”
Section: Introductionmentioning
confidence: 99%